Perbandingan Hasil Analisis Tingkat Bahaya Erosi Antara Metode Usle dan Rusle Di Sub Das Kapuas Hulu - Paraya, Mario Igor; Yulianto, Eko; Soeryamassoeka, Stefanus Barlian (Jurnal Teknologi Lingkungan Lahan Basah, 2025)
Abstract: The Kapuas Hulu Sub-watershed is a vital part of the Kapuas River ecosystem, facing the risk of soil erosion due to human activities and environmental factors This research seeks to.compare the results for erosion level analysis using the Universal Soil Loss Equation (USLE) and the Revised Universal Soil Loss Equation (RUSLE) methods.. The analysis is based on rainfall data, topography, soil type, and land cover, processed using Geographic Information Systems (GIS).In the USLE method, Bols erosivity is used as the basis for analy-sis. In the RUSLE method, surface runoff erosivity is calculated using runoff discharge from the Nakayasu Synthetic Unit Hydrograph (HSS Nakayasu) with a return period of Q100 and surface runoff volume using the SCS-CN method.Based on the analysis, USLE method produces a total erosion result of 87,865.414 ton/hectare/yr, while RUSLE method results in an erosion result of 55,558.402 ton/hectare/yr. This comparison shows that the erosion value estimated using RUSLE is approximately 0.6 times lower than that of USLE.The eroded land area in both methods is the same, at 579,955.035 hectares, indicating that the difference lies only in the estimated erosion rate, not in the distribution of the affected area. The USLE method yields a higher erosion value than the RUSLE method, suggesting that these two methods have different approaches in calculating the factors influencing erosion rates, with RUSLE generally providing lower estimated values